Nutritional Status and Intelligence Quotient of Preschool Children in Sunsari, Nepal - Rai, Munawatee; Choudhary, Ramanand; Deo, Binod Kumar; Baral, Dharani Dhar (Birat Journal of Health Sciences, 2021)
Introduction: Nutritional status has vital role on brain development of children during pregnancy and the first two years of life. Children who suffered from early childhood malnutrition have generally been found to have poorer IQ levels.Objective: To find out Nutritional Status and Intelligence Quotient of Preschool Children in Bhutaha VDC, Sunsari, Nepal.Methodology: A descriptive cross sectional design was used for the study. Proportionately 250 preschool children were selected. Data was collected by using self developed semi structured questionnaires for socio-demographic profiles, stadiometer and weighing scale for height and weight measurement respectively. Nutritional status was classified according to World Health Organization (WHO) standard. For an assessment of IQ, Indian Adaptation of Vineland Social Maturity Scale (VSMS) and Developmental Screening Test (DST) scale were used. These scales provide an estimate of social quotient (SQ) and development quotient (DQ) and are designed to measure social maturation of age group 'below 15 years'.  Data were analyzed using Pearson chi-square.Result: Among all, 51.2% of the children were male and most (80%) of the children were from Muslim ethnicity. Mean ± SD age of the children was 51.80±12.31 months. Almost all i.e., 98.4% of the children were delivered by normal vagina delivery and majority i.e., 78% of the children were delivered at home. Nearly equal proportions of children were from nuclear and non nuclear family. Prevalence of stunting and wasting were 28.4% and 8.4% respectively. Among 250 children, 11.6% had superior IQ, 52.4% had bright normal and 36% had average IQ. Mother’s education and malnutrition of children were significantly associated with IQ of children i.e., p=0.006, p=0.011 respectively.Conclusion: Mother’s education has great impact on Intelligence Quotient of children. Intelligence is strongly related to nutritional status. Poor nutrition leads to poor IQ, which results in poor academic achievements. To prevent this, priority should be given for the prevention of malnutrition which ultimately improves the intelligence of children.